Need Analysis for Developing English Teaching Materials Using the Eco-ELT Approach to Enhance Environmental Literacy Among High School Students in Dompu Regency - Bulan, Arif; Ramadhan, Risca Ariska; Wahyuni, Nur (Yayasan Pendidikan Bima Berilmu, 2024)
This research aims to analyze the need for developing English teaching materials using the Eco-ELT (Ecological English Language Teaching) approach to increase environmental literacy among high school students in Dompu Regency. There are three main focuses in this research: (1) students' English learning characteristics, (2) students' English learning needs, and (3) obstacles faced by teachers in implementing environment-based learning. The research method used is a qualitative descriptive method, with data collection through interviews. The research results show that students have various learning characteristics which are influenced by motivation, teaching methods, and the availability of learning resources. Students need relevant, contextual and interactive learning materials to improve practical skills in English. In addition, it was found that teachers face a number of obstacles, including a lack of adequate facilities, resources and professional training. Thus, this research concludes that there is an urgent need to develop English language teaching materials based on Eco-ELT. This approach not only helps in improving students' English language skills but also fosters environmental awareness and literacy among high school students in Dompu Regency. The implications of these findings can be the basis for developing more effective and sustainable curriculum and learning strategies.